Experimentation of the Process Parameters on FSW using Aluminum Alloy AA2014 and Copper - T Vijay Kumar, Dr. P.V.R Ravindra Reddy, Dr. A.Krishnaiah, R.ChandraSekhar Reddy (International Journal of Advanced Science and Technology, 2020)
FSW (Friction Stir Welding) is an emerging solid state joining process with great ability as joint quality is exceptionally high and the process is very repeatable. These geometries are used extensively in aerospace vehicles, transportation industry and pressure vessels. Friction stir welding is applied to the join two pipes, thin-walled, thickness variable hollow hemispheres. In this project, the Aluminum alloy AA 2014 and Copper plate of 5 mm thickness are welded together in butt joint geometry by friction stir welding (FSW) process. Process parameters such as welding speed, tool rotational speed and tilt angle play an important role to obtain a better weld joint for dissimilar metals/materials. The friction stir welding tool is one of the critical components to the success of this process. It consists of a cylindrical shoulder and a pin with different geometry. In this experimental work, the tool has been adopted with cylindrical tapered for friction stir welding of the dissimilar metal plates. FSW has been carried out at welding feed rate varying from 10 mm/min to 40 mm/min and tool rotational speed from 800 rpm to 2000rpm. Effects of the process parameters on butt welded joint are investigated for weld strength and hardness.In this project, we made a weld joint between aluminum alloys AA2014 similar metals and AA2014 & copper dissimilar using FSW by cylindrical tapered tool and welding parameters. We were adopted design procedure of friction stir welding from standard published journals example else weir, etc., and we compared mechanical properties of weld joint influenced by FSW by conducting different experimentation and also discussed on micro structural evolution of weld joint. The FSW of aluminum alloy and copper with butt joint geometry would be useful in the automobile and aerospace applications by getting the benefits from each material in a functional way.